The Link Between The Opportunistic Gut Fungal Pathogens With Colorectal Adenocarcinoma - Aisyah, Yunus; Norfilza, Mohd Mokhtar; Raja Affendi, Raja Ali; Siti Maryam, Ahmad Kendong; Hajar Fauzan, Ahmad (2023)
In Malaysia, colorectal cancer (CRC) is highly prevalent. The complex etiopathogenesis of CRC involves gut mycobiome. To date, little has been known about the composition and characteristics of the gut mycobiome in Malaysian CRC patients. We aimed to explore the presence of gut fungal pathogens in CRC patients.